Age and sex affect the association of systolic blood pressure with clinical outcomes in thrombolysed stroke patient: a secondary analysis of the INTRECIS study - Liu, Bai-Jun; Li, Jing; Chen, Hui-Sheng (Frontiers in Neurology, 2023)
Background and purpose Blood pressure is associated with outcomes in acute ischemic stroke (AIS) patients receiving intravenous alteplase. The study aimed to explore the effect of sex and age on their association. Methods Based on a prospective cohort, we retrospectively enrolled consecutive AIS patients who received intravenous alteplase and had complete blood pressure data, including baseline systolic blood pressure (SBP 01), SBP at 1 h (SBP 02), and SBP at 24 h (SBP 03) after alteplase. Maximum SBP (SBP max), minimum SBP (SBP min), and mean SBP (SBP mean) were calculated. Poor outcome was defined as having a modified Rankin Scale (mRS) score of 2–6 at 90 days. We explored the effect of age and sex on the association of different SBP indicators with the 3-month outcomes. Results A total of 1,593 eligible patients were included in the present study. All SBP indicators were found to be higher in patients with poor vs. good outcomes. Multivariate logistic regression analysis showed that all SBP indicators except baseline SBP were associated with poor outcomes with good prediction powers (AUC, 0.762–0.766). More SBP indicators (SBP 02, SBP 03, SBP min, and SBP mean) were associated with poor outcomes in women vs. men, while all SBP indicators after alteplase were associated with poor outcomes in patients aged ≥ 60 years, but none was seen in patients aged < 60 years. Furthermore, all SBP indicators after alteplase were associated with poor outcomes in women aged ≥ 60 years, while only SBP 03 in men aged < 60 years. Conclusion Among Chinese stroke patients treated with intravenous alteplase, SBP after alteplase was associated with clinical outcomes, which were affected by age and sex.